2022
DOI: 10.3390/antiox11101949
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Oral Vitamin C Prior to and during Myeloablative Chemotherapy and Autologous Haematopoietic Stem Cell Transplantation: A Pilot Study

Abstract: Chemotherapy-related side effects are common in patients undergoing myeloablative chemotherapy and haematopoietic stem cell transplantation. Some, such as oral mucositis, are believed to be due to enhanced oxidative stress and inflammation. Vitamin C, a potent antioxidant with anti-inflammatory properties, becomes severely depleted following myeloablative chemotherapy. The aim of our study was to assess the feasibility and efficacy of oral vitamin C supplementation to restore and maintain adequate vitamin C co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Although other inflammatory markers, such as interleukins 6 and 10, were measured for a subgroup of participants, the lack of overall elevations at baseline precluded assessing whether the micronutrients had a positive impact on those inflammatory levels. 67 Measurements of blood pressure and pulse showed no changes over time, providing further safety data for micronutrient treatment during pregnancy.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Although other inflammatory markers, such as interleukins 6 and 10, were measured for a subgroup of participants, the lack of overall elevations at baseline precluded assessing whether the micronutrients had a positive impact on those inflammatory levels. 67 Measurements of blood pressure and pulse showed no changes over time, providing further safety data for micronutrient treatment during pregnancy.…”
Section: Discussionmentioning
confidence: 81%
“…66 Blood tests suggested that increased micronutrient intake resulted in meaningful increases in vitamins B12 and D, with other research on this sample documenting that there were fewer women developing vitamin C deficiency for those in the micronutrient group compared with placebo. 67 The reduction in homocysteine in the micronutrient group provides insight into one potential mechanism of action in that the micronutrients may positively affect the methylation cycle, a cycle that supports the production of glutathione, an important antioxidant. Although other inflammatory markers, such as interleukins 6 and 10, were measured for a subgroup of participants, the lack of overall elevations at baseline precluded assessing whether the micronutrients had a positive impact on those inflammatory levels.…”
Section: Discussionmentioning
confidence: 99%
“…Prevents acute graft-versus-host disease (aGVHD), improves mucosal injury, ameliorates chemotherapy-induced mucosal damage improve diarrhea and anorexia after engraftment Maintains butyrate-producing bacterial population, reduces gastrointestinal toxicity [69][70][71][72][73][74] 6.1. Vitamins 6.1.1.…”
Section: Amino Acids Maintains Hscs Reduces Iatrogenic Complications ...mentioning
confidence: 99%
“…One study reported that oral vitamin C supplementation temporarily restores and maintains adequate vitamin C concentrations (1 g twice daily) in patients undergoing myeloablative chemotherapy and stem cell transplantation. However, intolerance issues were reported in patients one week after chemotherapy treatment [72]. Thus, intravenous vitamin C may be a better treatment choice.…”
Section: Vitamin Cmentioning
confidence: 99%
“…As a result, HSCT patients are prone to developing oral mucositis. Studies found that the incidence of oral mucositis in autologous HSCT patients is approximately 35.0% to 75.0% [3,4] .…”
Section: Introductionmentioning
confidence: 99%